Restoring range of motion in reduced acetabular version by increasing femoral antetorsion – What about joint load?. (July 2021) - Roth, Tabitha; Rahm, Stefan; Jungwirth-Weinberger, Anna; Süess, Janine; Sutter, Reto; Schellenberg, Florian; Taylor, William R.; Snedeker, Jess G.; Widmer, Jonas; Zingg, Patrick
Abstract: Background: Acetabular retroversion results in reduced range of motion, and is thought to contribute to femoroacetabular impingement. Severe retroversion can be corrected with a periacetabular osteotomy, which is a technically demanding intervention. In this study, we investigated whether increasing femoral antetorsion is a potential alternative to restore the range of motion and how this approach would affect hip joint loading. Methods: Six different finite element models of the same subject were built from MRI and used to simulate different load scenarios during stance phase, including healthy and pathological configurations with different acetabular version and femoral torsion angles. The subject's gait was analysed in our gait lab and motion data as well as joint reaction forces were integrated into the model. Hip range of motion, hip abductor muscle forces as well as localization and magnitude of hip joint loads were determined. Findings: The negative effects of acetabular retroversion on hip range of motion including flexion and internal rotation can be reversed by increasing femoral anteversion. The rotation of the femur furthermore affected muscular functionality by shortening the moment arms of the hip abductor muscles, resulting in increased abductor muscle forces, joint reaction forces and hip joint loading. Interpretation: Even though increased femoral antetorsion can compensate for the loss of hip range of motion due to reduced acetabular version, rotational ostotomy of the proximal femur is likely to alter muscular moment arms and therefore increase hip joint load, conflicting the goal of a long-term healthy joint. Highlights: Increasing femoral antetorsion can compensate for impaired range of motion. Hip abductor moment arm lengths need to be considered in rotational osteotomies. Increasing femoral antetorsion was associated with pronounced hip joint load.